(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Chromuim (III) complexes; antimicrobial activity; Artemia salina L. Bangladesh j. genet. biotechnol. 5 (1&2): 49-52, 2004 (June & December)